You Selfie, Therefore We Are: Indonesian Contemporary Art Consumption, Production and It's Dynamics - Salima Hakim (Graduate School of Institut Seni Indonesia Yogyakarta, 2017)
There has been a significant growth of enthusiasm and audience in the contemporary art events in Indonesia for the past ten years. Technology today plays a big role in creating complex yet dynamic relations between the audience, the artwork and the artist. It is widely recognized that nowadays, selfies are a common ritual also seen in art exhibitions and is often at the core of how the audience consumes and interacts with the artwork and the artist. This research will seek to examine how selfie as method of art consumption changes the function, relation as well as dynamics between the audience and the artwork as a mean of identity construction. Furthermore, this article will also try to investigate how selfie, as method of contemporary art consumption, to a certain extend influence or even determine the production aspect of the artwork done by contemporary artists, particularly in the Jakarta Art Scene.